Exploring Customer Technology Adoption Behavior for the Usage of E-Money in Indonesia: Mediating Role of Agent Credibility in the New Normal Era - Sunarjo, Wenti; Nurhayati, Siti; Setyanto, Refius Pradipta; Suroso, Agus (The Journal of Behavioral Science, 2023)
People are increasingly experiencing changes due to technological developments, such as those in payment methods using e-money. However, technological uncertainty still remains for users. The credibility of e-money agents could help convince users and increase the intention to use e-money. This research used survey questionnaires to collect data from 510 e-money user residents of Central Java and the special region of Yogyakarta, Indonesia. Structural equation modeling technique was used to analyze data. The results showed a model fit for the study: χ2/(df) = 2.87, GFI = 0.95, AGFI = 0.92, NFI = 0.97, CFI = 0.98, and RMSEA = 0.06. Results showed perceived technological uncertainty (PTU) has a direct significant positive effect (β = .24, p = .00) on the agent credibility (AC) of e-money. The mediation test showed PTU has a significant effect (β = .52, p = .00) on customer technology adoption behavior (CTAB) through AC. Knowledge of technology (KT) has a direct significant positive effect (β = .29, p = .00) on AC. However, mediating effect between KT and CTAB has an insignificant effect through AC (β = .32, p = .07). Also there is direct significant positive effect between AC and CTAB (β = 1.12, p = .00), and between CTAB and continuance usage intention (β = .68, p = .00). These results show that the influence of agency credibility is indispensable as a mediating factor that can encourage and influence the use of e-money usage by people.